Long-term stability of trastuzumab in plasma and whole blood samples stored under different conditions - Jonathan González-García; Fernando Gutiérrez-Nicolás; Gloria Julia Nazco-Casariego; María Micaela Viña-Romero (Elsevier, 2019)
Objective: The present work analyzed the stability of trastuzumab concentrations in blood and plasma samples stored at 4 °C and -20 °C. Method: Blood samples of patients treated with trastuzumab (Herceptin ®) were analyzed. Stability of trastuzumab was analyzed under different conditions: whole blood stored at 4 °C during 72 hours, blood plasma stored at 4 °C during 120 hours and blood plasma stored at -20 °C during 365 days. Results: In whole blood trastuzumab concentration at 72 hours was 99.01 ± 0.02%, and in plasma samples at 120 hours it was 98.6 ± 2.0%. The concentration of trastuzumab was 95.22 ± 3.20% after 12 months' storage at -20 ºC. Conclusions: The concentration of trastuzumab remains stable for at least 72 hours in whole blood stored at 4 °C, five days in plasma stored at 4 °C and one year in plasma stored at -20 °C.